EFFECTIVENESS OF THE ROLE OF PROGRAM COMMUNITY FACILITATORS NATIONAL AFFORDABLE HOUSING PROGRAM (NAHP) MINISTRY OF PUPR IN BALI PROVINCE - Aurellia Tifani; Anwar; Agung Widhi Kurniawan; Romansyah Sahabuddin; Muhammad Ilham Wardhana Haeruddin (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2023)
The National Affordable Housing Program (NAHP) implemented by the Ministry of PUPR (Public Works and Public Housing) aims to address housing affordability issues in the province of Bali. As part of the program, program community facilitators play a crucial role in facilitating the implementation and ensuring the program's effectiveness. Therefore, it becomes essential to evaluate the effectiveness of these facilitators in achieving the program's objectives. This study aims to determine the effectiveness of the role of program community facilitators National Affordable Housing Program (NAHP) Ministry of PUPR in the Province of Bali. The type of research used is descriptive qualitative. Descriptive provides a systematic description of cycles, problems, phenomena, services, programs, or information to individuals or groups wishing to study. The findings of this study explain the effectiveness of the role of the program has been achieved. The results of interviews with co-facilitators and beneficiary communities assessed the effectiveness of program understanding, target accuracy, timeliness, goal attainment, and real changes from the results of interviews with co-facilitators and beneficiary communities.